Influence of carbohydrate correction of raw materials on the growth of lactic acid microorganisms in the process of directed fermentation of vegetables - J. A. Semenova; N. E. Posokina; V. I. Tereshonok (Овощи России, 2020)
Relevance. The use of certain single or mixed cultures of lactic acid microorganisms and the mandatory control of the fermentation process of white cabbage are of great importance to ensure that the product is of stable quality without the need for any chemical preservatives or harsh processing conditions. Carbohydrates contained in raw materials play an important role in this process, since carbohydrates are the main source of maintaining the viability of lactic acid microorganisms. By adjusting the carbohydrate component of raw materials at different stages of fermentation, it is possible to maintain a high titer of microorganisms, while obtaining not only a high-quality product, but also giving it, along with prebiotic (a source of fiber) and probiotic properties. Materials and methods. The purpose of this research work was to ensure the direction of the biotechnological process in the direction of stabilization of the concentration of functional microflora (starting systems of lactic acid microorganisms), under the influence of introduced carbohydrate nutrients. In this work, we studied two fermentation systems of microorganisms that are fundamental microorganisms in the fermentation of cabbage, namely, systems consisting of a pre-fermentation culture of Leuconostoc mesenteroides and one of the cultures of lactobacilli: Lactobacillus plantarum or Lactobacillus brevis. The study used the usual microbiological method for determining the number of microorganisms by seeding in an agarized culture medium, as well as processing experimental data. Results. As a result, we found that the introduction of a carbohydrate Supplement allows us to stabilize the dynamics of changes in the concentration of the studied starting systems at the same initial level throughout the main stage of fermentation.